Sistema integrado de informações para preservação de recursos hídricos em unidades de conservação - Souza, Lucy Mary Soares (2010)
The increasing demand of mankind by use of water quality and sufficient volume to meet their needs in their different uses, shows that water resources must be managed and preserved. A watershed is the physical unit that integrates the entire flow of water that makes up the hydrological cycle, but its use is being carried out in a disorderly way, without complying with the compliance of their characteristics and fragilities. Brazil has a very advanced legislation regarding the environment, especially related to water, and a growing awareness of the need to demarcate areas in order to safeguard the different ecosystems found in this vast territory. In Brazil, many of the areas selected to include environmental protection within its boundaries major resources stocks. However, deforestation and poor land use along these water resources may affect and jeopardize the supply and quality of water throughout their watersheds, affecting populations downstream. The purpose of this paper is to present an Integrated Information System, embodied in a Geographic Information System (GIS), which adds the elements required for management and conservation of water resources in protected areas. In the development of GIS will be used the new structure and Geographical Data Vector (EDGV) and the Geospatial Metadata Profile of Brazil (MGB), approved in 2008 by the National Cartography (Conc), aiming to standardize the structures spatial data, facilitating data sharing, interoperability and rationalization of resources among data producers and users of geospatial information. In the proposed system shows that the systematic organization into a Geographic Information System (GIS) of water resources and the various elements and factors about them impacting facilitates the analysis and subsequent management of water resources conservation units (CUs). Through these spatial analysis and comparative data were obtained as a result of the making of a final map containing an indication of inharmonious elements in the area. Indicated the best places to collect water in order to assess its quality and, eventually, we proposed a new limit for the conservation unit. The final map will serve as support for management to operate and monitor the areas according to their real possibilities and implement corrective measures and mitigation. Additionally, information based on the database associated with the GIS will enable the integration of various public and private entities that deal with specific issues, enabling interoperability and cooperation between them, as well as confirming that the use of Geotechnology is an appropriate option for the best management of the areas involved. The techniques and procedures used can be applied in the management of water resources from other areas. We used the União Biological Reserve - Rebio Union - located in the State of Rio de Janeiro, as a case study.